Analisis Pandangan Mazhab terhadap Putusan Hakim kepada Anggota Militer sebagai Fasilitator Pelaku Tindak Pidana Narkotika - Putri Anisa; Hamzah Hasan (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab dan Hukum, 2021)
The main problem in this research is about legal considerations in making decisions against members of the military who carry out criminal acts and how Islamic law regulates the sanctions or laws that will be given by narcotics abusers even though at the time of the Prophet there was no such case. The type of research used is qualitative research or methods (field acceptance), namely research that provides a qualitative picture where it is focused on field research methods and their relationship with contemporary Islamic law. This research is sourced from secondary data and primary data with primary primary data sourced from interviews of judges at Military Court III-16 Makassar. From the research conducted, the results show that: (1) In enforcing the criminal law against military personnel who commit narcotics crime, it is still regulated in the law. No. 35 of 2009 concerning Narcotics, in accordance with the case number 064-K / PM.II-09 / AU / III / 2017 by being subjected to the main law and an additional sentence of 1 year and dismissed from military service. (2) factors that cause the organization of the perpetrators of a crime, namely internal and external factors such as family, psychological and personal factors. In a personal factor, the syringe happens only part of the way. (3) law enforcement according to the imam of the mazhab against narcotics crime found in this case which occurred based on these findings was based on this. At the time of the Prophet there was no such thing as drugs so that it was confirmed to be khamar. Sanctions given are in the form of hada and ta'zir penalties in accordance with the criminal act committed.Keywords: Judges' Decisions ; Military ; Narcotics Criminal